Extractive Taxation and the French Revolution - Tommaso Giommoni; Gabriel Loumeau; Marco Tabellini (Institute of Labor Economics (IZA), 2025)
We study the fiscal determinants of the French Revolution, exploiting plausibly exogenous variation in the salt tax - a large source of royal revenues and one of the most extractive forms of taxation of the Ancien Régime. Implementing a Regression Discontinuity design (RDD), we find that parts of France subject to a higher salt tax experienced more revolts against the monarchy between 1750 and 1789. These effects already appear in the 1760s, but become stronger over time and peak in the 1780s. Combining the RD model with variation in local weather conditions during the 1780s, we document that droughts amplify the effects of the salt tax on revolts by increasing wheat prices and activating latent discontent. Then, we connect the discontent generated by the salt tax to the French Revolution. First, we provide evidence that riots spread more quickly in high tax areas. Second, we show that areas burdened by a higher salt tax report more complaints against the salt tax in the list of grievances collected by the king in the spring of 1789. Third, we document that legislators representing areas with a higher salt tax are more likely to demand the end of the monarchy and to support the death penalty for the king.
Keywords: D74; H20; H31; O23; 330; French Revolution; regime change; extractive taxation; state capacity